1999
DOI: 10.1128/aac.43.8.1961
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Insertion Mutations between Codons 67 and 70 of Human Immunodeficiency Virus Type 1 Reverse Transcriptase Confer Multinucleoside Analog Resistance

Abstract: To investigate the occurrence of multinucleoside analog resistance during therapy failure, we surveyed the drug susceptibilities and genotypes of nearly 900 human immunodeficiency virus type 1 (HIV-1) samples. For 302 of these, the 50% inhibitory concentrations of at least four of the approved nucleoside analogs had fourfold-or-greater increases. Genotypic analysis of the reverse transcriptase (RT)-coding regions from these samples revealed complex mutational patterns, including the previously recognized codon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(74 citation statements)
references
References 35 publications
3
70
0
1
Order By: Relevance
“…We think the answer is more complex. A recent study showed that the insertion mutations provide multidrug resistance mainly when they are present in a background of AZT resistance mutations [71]. Our experiments show that the enhanced phosphorolysis associated with the D67N/ K70R/T215F/K219Q RT is relatively specific for AZT-terminated DNA [46].…”
Section: Hiv-1 Multidrug Resistancementioning
confidence: 54%
“…We think the answer is more complex. A recent study showed that the insertion mutations provide multidrug resistance mainly when they are present in a background of AZT resistance mutations [71]. Our experiments show that the enhanced phosphorolysis associated with the D67N/ K70R/T215F/K219Q RT is relatively specific for AZT-terminated DNA [46].…”
Section: Hiv-1 Multidrug Resistancementioning
confidence: 54%
“…In the case of mutations K65R and L74V, both selected by ddI, an 84-fold loss in the catalytic rate constant of the double-mutated RT compared to the WT also accounts for the poor ability to use natural dNTPs and the resulting poor viral fitness [129] and explains why K65R and L74V are never selected together in the clinic [48]. Finally, clinical data revealed that K65R hypersensitizes HIV-1 to AZT [55,95,130] and does not develop in patients receiving AZT-containing regimens [131]. Accordingly, in a more recent clinical study, a low frequency of K65R mutation emerged, in treatment-experienced patients, but only for patients without detectable TAMs at baseline, suggesting a functional and/or structural incompatibility for the two substitutions within the same RT.…”
Section: Mutation L74vmentioning
confidence: 94%
“…ddI [89], and also contributes to resistance to each of the NRTIs in the context of TAMs [60,[90][91][92][93]. In about 2% of heavily treated HIV-1-infected patients [94] having received prolonged AZT treatment followed by administration of other NRTIs, RT has a dipeptide insertion (SA, SG or mainly SS) between position 69 and 70, associated with other amino acid substitutions such as T69S or T215Y and other TAMs [94][95][96]. Individually, the dipeptide insertions confer only a low level of resistance to each of the NRTIs, but in the context of T215Y and other TAMs, high levels of resistance to AZT and moderate levels to d4T, ddC, ddI and tenofovir are achieved [95][96][97][98][99] ( fig.…”
Section: Emergence Of Resistance Mutationsmentioning
confidence: 99%
“…Insertion mutations between positions 69 and 70 of the fingers domain (69-insertions) have been described that result in multidrug-resistant HIV [50]. These mutations are associated with NAMs in clinical isolates [51].…”
Section: Nucleoside Rt Resistance Due To Excisionmentioning
confidence: 97%
“…5a). Each monomer of the protease also contributes amino acids (positions [45][46][47][48][49][50][51][52][53][54][55][56] to form a flap that extends over the substrate-binding cleft. The flap must be flexible enough to allow entry and exit of the polypeptide substrates.…”
Section: Protease Inhibitor Resistancementioning
confidence: 99%